2020
DOI: 10.21873/anticanres.14493
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Induces Cytotoxicity in Mix Cellularity Classical Hodgkin's LymphomaviaCaspase Activated-cell Death

Abstract: Background/Aim: We investigated the effects of luteolin (LUT) on classical Hodgkin's lymphoma (cHL), since such studies in malignant lymphomas are lacking. Materials and Methods: Effect of LUT on cell growth was assessed with water-soluble tetrazolium 1 (WST-1) cell proliferation assay and automated hemocytometry on trypan blue-exclusion assay. Cell death was investigated with acridine orange/ethidium bromide live-dead assay, propidium iodide (PI) flow cytometry, and Annexin-V-PI microscopy. Caspase activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Besides, we also found that when combined with R-CHOP, QHF can significantly lower the overall side effect frequencies and improve the short-term effects of R-CHOP in treating initial onset DLBCL patients [ 24 ]. In addition, we explored the effects of several major flavonoids of QHF in vitro and found that wogonin, luteolin, kaempferol, quercetin, and silymarin can inhibit the proliferation and induce apoptosis of the Raji, SU-DHL-4, and A20 cell lines (data not published), which is consistent with other studies [ 25 28 ]. Therefore, we hypothesized that QHF can enhance the antitumor effects of chemotherapy by modulating immune functions, especially the tumor immune microenvironment (TIME), of B cell NHL.…”
Section: Introductionsupporting
confidence: 88%
“…Besides, we also found that when combined with R-CHOP, QHF can significantly lower the overall side effect frequencies and improve the short-term effects of R-CHOP in treating initial onset DLBCL patients [ 24 ]. In addition, we explored the effects of several major flavonoids of QHF in vitro and found that wogonin, luteolin, kaempferol, quercetin, and silymarin can inhibit the proliferation and induce apoptosis of the Raji, SU-DHL-4, and A20 cell lines (data not published), which is consistent with other studies [ 25 28 ]. Therefore, we hypothesized that QHF can enhance the antitumor effects of chemotherapy by modulating immune functions, especially the tumor immune microenvironment (TIME), of B cell NHL.…”
Section: Introductionsupporting
confidence: 88%
“…So far, some of these ingredients have been well described for their anti-lymphoma effects in experimental studies. luteolin, an active ingredient extracted from Codonopsis Radix and Pseudostellariae Radix, has been tested to inhibit the proliferation of classical Hodgkin’s lymphoma cells via caspase activation ( Gharbaran et al, 2020 ). Quercetin, an active ingredient of Astragali Radix and Glycyrrhizae Radix et Rhizoma, has been detected to inhibit cancer cell growth by modulating AKT and NF-κB pathways in lymphoma models ( Soofiyani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin is a yellow ketone, which exists in many foods, has powerful anticancer ability, has been widely used in a variety of human malignant tumours [27], can trigger apoptosis, inhibits the growth of cells, stimulates the stagnation of the cell cycle, and prevents cell migration. Studies have proved that luteolin is induced by caspase activation, causing cell death due to cell toxicity [28]. Kaempferol has been shown to exert anticancer activity through multiple pathways, such as inhibiting angiogenesis and expression of vascular endothelial growth factor (VEGF), inducing apoptosis, and regulating HIF-1α [29].…”
Section: Discussionmentioning
confidence: 99%